Study of the efficiency of using disinfectants «Adalux» to provide paper material with bactericidal properties - Zinchenko, I; Babich, Olena V; Tsytlishvili, K; Shostenko, O; Kononenko, K (Annals of Mechnikov’s Institute, 2020)
Introduction. The issue of environmental management and protection of the environment from pollution are of paramount importance. Today, there is a big problem associated with the accumulation of polymer waste, which catastrophically pollutes the planet. Most plastic waste is not recyclable, but can be decomposed in landfills for decades. As an alternative to plastic products, world experts suggest the use of paper, biodegradable (biopolymer), reusable packaging. Many countries are now working to develop and produce packaging from affordable and environmentally friendly and natural materials that can degrade in soil or compost. The purpose of this work is to determine the resistance of paper samples of different densities to microbiological contamination after treatment with bactericidal agent «ADALUX». Objects of research - samples of paper which are widely used in the industry, with a density of 80 g/cm2, 52 g/cm2, 50 g/cm2; liquid bactericidal drug «ADALUX» (hereinafter - the drug) - a disinfectant that does not contain chlorine compounds. Research methods and techniques. The paper samples were treated with a 0.1% solution of the drug in the form of an aerosol and stored at room temperature for a month and monitored. Raw paper samples were stored in the same conditions. The study of samples for microbiological contamination was performed for 7, 14 and 30 days on the following indicators: total microbial count (ТMC), bacteria of the Escherichia coli group (BЕCG), enterococci (EC), fungi and yeast-like microorganisms. The resistance of paper samples to microbiological contamination, or bactericidal properties of the paper treated with the drug, was determined by the following methods: contact (disk), agar filling, artificial contamination of the paper surface - test object - Escherichia coli B (hereinafter - E. coli В). By comparing the number of colonies that grew in the variants with treated and untreated paper samples, the resistance of the test paper samples to high bacterial contamination was determined. Results and discussion. On paper samples that were not treated with an antibacterial agent, growth of saprophytic bacteria (GSB) was observed during the storage period, mold and yeast-like fungi were also found, and a small number of bacteria belonging to the group of E. coli were found. Processing of paper samples with 0.1% solution «ADALUX» provided bactericidal and bacteriostatic properties of the paper. They especially manifested themselves on the day of treatment and after 7 days of storage. Bacteriological crops from the surface of the samples on the day the paper was treated with a bactericidal agent showed a complete absence of microorganisms on the surface of all the studied paper samples. After 7 days of storage, the contamination of the treated samples with saprophytic microorganisms was observed 1.6 - 2.9 times less than in untreated ones. After 14 and 30 days of paper storage, the bactericidal effect against TMC and BЕCG decreased, but the development of bacteria on the surface of the samples was slower than on untreated paper samples. Molds and yeast-like fungi were observed on both processed and untreated paper samples of various densities. Probably, the 0.1% solution «ADALUX» has a more pronounced bactericidal effect, but its fungicidal properties are much less. Microscopic studies of colonies grown on a selective medium for fungi showed a predominance of growth of yeast-like fungi and less mold. On all investigated paper samples (processed and unprocessed), stored for more than 14 days, colonies of microorganisms belonging to spore bacteria were identified. Morphological features and microscopy of the colonies of these microorganisms suggested that they belong to the spore bacteria of the genus Bacillus, tentatively of the species - Bacillus subtilis (hay bacillus), which are widespread in the environment. Due to the ability to form spores, these microorganisms easily tolerate adverse living conditions and continue to live on the surface of the paper. After processing paper samples with «ADALUX» disinfectant (0.1% solution), paper with a density of 80 g/cm2 had the most bactericidal properties, least of all with a density of 50 g/cm2. A study of the resistance of treated paper samples to artificial bacterial contamination with the Escherichia coli B test-object (at a concentration of 103 - 106 cells/ml) showed that after 7 days of storage, there was no growth of the test object on paper samples with a density of 80 g/cm2 and growth retardation on paper samples with a density of 52 g/cm2. Studies of paper samples during storage for 30 days showed that all paper samples (processed and unprocessed) did not have resistance to artificial bacterial contamination upon contact with the test object, which resulted in fouling of paper samples with colonies of E. coli bacteria. Conclusions. Based on the results, it was found that the disinfectant «ADALUX» (chlorine-free) in a concentration of 0.1% has a bactericidal effect when processing paper samples for seven days and bacteriostatic effect (inhibition of bacterial growth) when stored for a month against saprophytic microorganisms and BЕCG, but not very effective against microscopic fungi. It is likely that paper products that have been treated with such a disinfectant, on the one hand, have bactericidal properties for some time, on the other hand, in case of impossibility of recycling after their direct use, as waste can decompose naturally without harming the environment. DOI: 10.5281/zenodo.4038886